Practice makes perfect? The European Union's engagement in negotiations on a post-2015 framework for development - Adam Moe Fejerskov; Niels Keijzer (Danish Institute for International Studies (DIIS), 2013)
2015 is the deadline by which the 193 UN Member States have committed to achieve the Millennium Development Goals and when discussions on a possible future framework will have to be concluded. Since the MDGs were designed in the 1990s the world has witnessed profound changes, and the negotiations towards 2015 are set to take place in a context marked by resource scarcity and financial restraints, and where the barriers for change and progress, as well as the opportunities, have changed significantly. For the European Union to maximise its influence on the negotiations leading up to 2015, it will have to learn from its past performance in international negotiations. Delivering a comprehensible and influential message in the UN, with political support from both EU and non-EU Member States will be a delicate process of internal coherence, gaining political support and building alliances. The report discusses the potential of EU influence in a post-2015 process that is at its core UN-led. It seeks to complement an analysis of the possible substance of a post-2015 framework, a subject evidently covered in current policy discussions and recent studies, with an analysis of the EU's on-going and future engagement in the process of negotiating such a framework. The latter aspect is not covered in detail in most of the on-going research on post-2015 processes, and this report explores to what extent useful lessons can be drawn from an analysis of the EU's engagement in recent EU negotiations.
Keywords: 300